Geochronology of the lpanema layered mafic-ultramafic complex, Minas gerais, Brazil: Evidence of extension at the meso-neoproterozoic time boundary - Angeli, W.; Teixeira, W.; Heaman, L.; Moore, M.; Fleet, M. E.; Sato, K. (V H Winston & Son Inc, 2004)
The mafic/ultramafic Ipanema Layered Complex (ILC), Minas Gerais Brazil, consists of seven individual bodies. These units crosscut polyphase orthogneisses and interlayered paragneisses of the Paleoproterozoic Juiz de Fora Complex. Intrusive granitoids tectonically related to [lie Neoproterozoie Aracuai orogen are also present in the study area.A Sm-Nd whole-rock linear array for seven samples metapyoxenites, metaperidotiles, metagabbro. and meta-anorthosite) from the Santa Cruz massif, the largest body of the ILC. suggest that it was emplaced at 1104 +/- 78 Ma the original magma was derived from a depleted mantle source (epsilon(Ndt)= +3.8). U-Pb single-grain zircon stud of a meta-anorthosite yields all upper intercept age of 1719 +/- 4 Ma, which is interpreted to represent inheritance. The lower intercept at 630+/-3 Ma indicates (hat a Neoproterozoic tectonothermal episode overprinted the ILC, this event occurred under upper-amphiolite-, to granulite-facies conditions. The 630 Ma episode is consistent with the timing of regional metamorphism and deformation of the adjacent Aracuai orogen (Brasiliano collage). Emplacement of the ILC and other coeval metamafies and meta-ultramafics (of alkaline affinity) in the re, oil is attributed to early extension tectonics, accompanying accretion of the Rodinia super- continent during the Mesoproterozoic-Neoproterozoic time boundary.